Analisis Gramatika Kata Kenosis Di Dalam Filipi 2:7 - Samuel Lengkong (EUANGGELION: Jurnal Teologi dan Pendidikan Kristen, 2021)
Theological debate about the word “kenosis, the question is what Christ emptied of Himself. Discussions about the Doctrine of Christ or Christology are indeed endlessly discussed and debated, both by heretics and by Christian apologists. In this study, two approaches are used, namely the study of literature and the study of the theological meaning of the phrase "emptied Himself" (εαυτον εκενωσεν) in Philippians 2:7, grammatically in the sentence in the verse, namely, "He emptied himself, and took the form of a servant,” (εαυτον μορφην ), there is the word “labon” (λαβων). The word “labon” (λαβων), is an “instrumental participle”, which means to express the means of action (real or unreal). The conclusion is that the word "kenosis" has the meaning of making an empty "space" in Him to be able to fill it with the nature of a servant and a human being. Thus, it is the nature of a servant and a human being that is seen by Christ in his relationship and interaction with humans and the world.